Clever Duck - "King, Smith Dick:" (Puffin Books: London, 1997)
Damaris, a bright young duck, and her sheepdog friend, Rory, devise a plan to teach a pompous old boar a lesson. But when the pigs break for freedom, they are captured. Out of pity, Damaris finds a way of returning them to the farm, and with bellyaches and bruises the herd finally comes home
Keywords: Children's stories-Domestic animals